THE EFFECT OF LEADERSHIP STYLE ON THE PERFORMANCE OF CIVIL SERVANTS IN THE JAMBI PROVINCIAL DEPARTMENT OF CULTURE AND TOURISM - rizki amalia; Nadia Evelyn (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2025)
Enhancing staff performance is mostly dependent on leadership. The motivation, discipline, and productivity of public servants can be impacted by the different leadership styles that leaders employ. It is believed that varying leadership styles are connected to the phenomena of disparities in performance outcomes between work units. This study uses a proportionate stratified random sample technique with 51 respondents to ascertain the degree to which leadership style affects the performance of public servants (PNS) at the Jambi Province Cultural Office. Descriptive statistics and hypothesis testing were used in the data analysis process. in these institutions, as evidenced by the study's findings that it contributes 65.8% to public servant performance. Other factors outside the purview of 34.2%.